“You Know How People Talk,” Reasons Behind Child Marriage among Female Youth in The North-Eastern State of West Malaysia - Md Alwi, Nadiah; Muhamad, Rosediani; Ishak, Azlina; Suwankhong, Dusanee (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Over the past decade, Kelantan has consistently ranked among the top three states in Malaysia for the highest number of registered child marriages, garnering attention in local and international news. However, little is understood about the local factors influencing girls’ decisions to marry young. This study aimed to explore these reasons from the perspective of young women involved in child marriages in Kelantan, Malaysia. MATERIALS AND METHODS: Fourteen women aged 16-30, married before 18, participated in semi-structured, in-depth interviews. The interviews were recorded, transcribed, and analysed using NVivo® software. Thematic analysis, drawing from phenomenology and socioecological theory, revealed three overlapping themes. RESULTS: Themes emerged were: (1) self-fulfilment, (2) marriage brings security, and (3) avoidance of public ridicule. CONCLUSION: The study underscores societal and familial pressures, alongside low socioeconomic status, and religious factors, as central to child marriage in Malaysia. By amplifying the voices of these women, efforts can focus on preventing the consequences and devising solutions to curb this practice in the future.